2016
DOI: 10.1016/j.nbd.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Protection by dietary restriction in the YAC128 mouse model of Huntington's disease: Relation to genes regulating histone acetylation and HTT

Abstract: Huntington’s disease (HD) is a fatal neurodegenerative disease characterized by metabolic, cognitive, and motor deficits. HD is caused by an expanded CAG repeat in the first exon of the HTT gene, resulting in an expanded polyglutamine section. Dietary restriction (DR) increases lifespan and ameliorates age-related pathologies, including in a model of HD, but the mechanisms mediating these protective effects are unknown. We report metabolic and behavioral effects of DR in the full-length YAC128 HD mouse model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 70 publications
2
22
0
Order By: Relevance
“…In addition, consistent with mutant Huntingtin accelerating cellular aging, a recent study reported an accumulation of epigenetic markers of aging in the brain of HD patients as compared to control subjects (Horvath et al, 2016). In line with this notion, several genetic, pharmacological and dietary anti-aging interventions have been reported to ameliorate aspects of HD in mouse models (Duan et al, 2003, Ma et al, 2007, Sadagurski et al, 2011, Tallaksen-Greene et al, 2014, Moreno et al, 2016). …”
Section: Discussionmentioning
confidence: 85%
“…In addition, consistent with mutant Huntingtin accelerating cellular aging, a recent study reported an accumulation of epigenetic markers of aging in the brain of HD patients as compared to control subjects (Horvath et al, 2016). In line with this notion, several genetic, pharmacological and dietary anti-aging interventions have been reported to ameliorate aspects of HD in mouse models (Duan et al, 2003, Ma et al, 2007, Sadagurski et al, 2011, Tallaksen-Greene et al, 2014, Moreno et al, 2016). …”
Section: Discussionmentioning
confidence: 85%
“…More recently we have observed that dietary restriction induces hypothalamic Cbp in mice, associated with protective effects against proteotoxicity [9]. Similarly, dietary restriction in Caenorhabditis elegans induces Cbp , and blocking this induction prevents protective effects of dietary restriction during aging [8].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently we assessed the correlation of hypothalamic Cbp with the protective effects of dietary restriction in a mouse model of Huntington's disease [50]. In this case the model of dietary restriction was every-other-day feeding, which does not entail net reduction in caloric intake (mice consume twice as many calories on the ad lib fed days).…”
Section: Discussionmentioning
confidence: 99%
“…In this case the model of dietary restriction was every-other-day feeding, which does not entail net reduction in caloric intake (mice consume twice as many calories on the ad lib fed days). This protocol completely protected against the motor impairments produced by the transgenic expression of the mutant Huntington transgene, correlated with induction of Cbp in the hypothalamus [50]. The next most obvious study was to functionally assess if experimental inhibition of hypothalamic Cbp would prevent protective effects of dietary restriction.…”
Section: Discussionmentioning
confidence: 99%